PENERAPAN TEKNOLOGI PENJERNIH AIR PADA KELOMPOK USAHA TAHU DALAM UPAYA PENINGKATAN KUALITAS TAHU DI KOTA BENGKULU - Irnanda Priyadi; Faisal Hadi; Khairul Amri (DHARMA RAFLESIA, 2018)
Clean water is one of the important components needed in the process of making tofu. Water sources in the city of Bengkulu, whether managed by PDAM or from dug wells with a depth of less than ten meters, have poor water quality. This will affect to the quality of tofu produced. And wiil be affect to the tofu bussiness development at Bengkulu city in the future time. One alternative solution to solve this problem was designed water purifier using solar cell technology with microcontroller to overcome the clean and hygienic water supply more economical. Specific targets to be achieved in this activity are patents products with affordable raw materials and prices. The results of the manufacturing of the purification module show the LCD reading of the water quality parameters used for the preparation of tofu prior to treatment using TDS sensor detection and pH sensor are 5,885 and 8,320. While the LCD reading after the treatment using TDS sensor detection and pH sensors are 4,901 and 7,763. Further laboratory test results on the performance of water purification module for the manufacture of tofu application showed an increase of TSS level. The next result, amount of the total Coli content is 551/100mL at the before and become 28/100mL at the after. Meanwhile, the conductivity is being increased from 459 at the before and become 469 at the after. Keywords: tofu business group, water purifier, solar cell technology, microcontroller.